Stratigraphic analysis of Brejo Santo Formation, Araripe Basin, Northeast Brazil: paleogeographic implications - Fambrini, Gelson Luís; Neumann, Virginio Henrique de Miranda Lopes; Barros, Cecilia Lima de; Silva, Sonia Maria Oliveira Agostinho da; Galm, Paulo Cesar; Menezes Filho, José Acioli Bezerra de (Geologia USP. Série Científica, 2013)
The Araripe Basin has been the subject of several publications in the recent years, notably with respect to the rich paleontological collection of Brejo Santo, Crato and Romualdo Formations. However, papers detailing stratigraphic aspects of Brejo Santo Formation are scarce. The formation (Mesozoic era - Dom João Stage) is represented by a predominantly pelithic succession (up to 450 m thick) outcropping in eastern portion of the basin. The Brejo Santo Formation unconformably overlies the Cariri Formation, presumably of Paleozoic age, and makes gradational contact with the overlying Missão Velha Formation. It consists of pelithes, such as massive to laminated reddish-brown chalks and calciferous shales with decimetric intercalations of white to greenish-grey siltstones and centimetric layers of reddish mottled, speckled and striped shales, with calcareous nodules, and subordinately, muddy limestones and highly fossiliferous calciferous sandstones and fine sandstones with planar cross-stratifications. The measured paleocurrents have a consistent dispersion pattern for SE, SW and S, suggesting the installation of an open wide basin toward the south. The facies and facies associations described were interpreted as generated by (i) lake systems in which periodically the level of the lakes and/or ponds suffered sudden variations, causing changes in coloration related to seasonal fluctuations in the level of the lake (periods of subaerial exposure) and (ii) ephemeral river systems which fed these lakes. The widespread occurrence of fossil organisms, such as non-marine ostracods and conchostracheans suggest that the sediments of Brejo Santo Formation were possibly deposited in lacustrine-fluviatile systems favorable to the formation of red beds layers, under hot climatic conditions with well-defined dry seasons, corroborating the depositional system interpretation.